2022
DOI: 10.3390/ijerph19052854
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Worksite-Based Self-Management Program in Traditional Retail Market Workers: Longitudinal Associations with Metabolic Parameters

Abstract: (1) Background: This study explored the effects of a worksite-based self-management program on metabolic parameters in traditional retail market workers during a 3-year period. (2) Methods: Seventy traditional retail market workers who completed 3 years of follow-up were included in this study. The worksite-based self-management program was developed to help traditional retail market workers manage metabolic parameters themselves based on the following content: (I) using a metabolic syndrome action checklist, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…Group discussion allows participants to exchange their positive experiences and figure out how to create their own plan of action [ 15 ]. Action checklists also increase participants’ confidence that they can change their lifestyle behaviors [ 32 ]. Previous studies reported that perceived self-efficacy in cardiovascular disease was positively associated with physical exercise, food choices, smoking habits, and health-related quality of life [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Group discussion allows participants to exchange their positive experiences and figure out how to create their own plan of action [ 15 ]. Action checklists also increase participants’ confidence that they can change their lifestyle behaviors [ 32 ]. Previous studies reported that perceived self-efficacy in cardiovascular disease was positively associated with physical exercise, food choices, smoking habits, and health-related quality of life [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 88.9% of proposed action plans were implemented within 3 months after the PAP-CCVH. A previous participatory study of traditional retail market workers [ 32 ] that used a similar action checklist reported an 82.7% implementation rate. The higher rate in our study may have been because the learning-by-doing action checklists used in our study were shortened to fit the needs and lifestyle of older people and so that the goals would be acceptable to the participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kadar gula darah puasa dan trigliserida menunjukkan penurunan dalam setahun selama tiga tahun, selain itu terjadi penurunan skor gangguan metabolic dan pemeliharaan parameter metabolisme pada rentang waktu 3 tahun. 15 Implementasi program menunjukkan kesuksesan. Hasil follow up 3 tahun menunjukkan terdapat perbedaan signifikan pada komponen risiko metabolic sindrom yaitu kadar glukosa puasa (2 = 18.52, p < 0.001), trigliserida (2 = 11.68, p = 0.009), dan skor metabolic syndrome (2 = 17.73, p < 0.001).…”
Section: Metodeunclassified
“…Lingkar perut mengalami penurunan signifikan pada satu tahun pertama (p = 0.009), kadar glukosa puasa (p = 0.005) dan trigliserida (p = 0.009) mengalami penurunan signifikan pada tahun pertama dan tahun kedua. 15 16 penelitian ini merupakan cross sectional study. 16 3063 pekerja di perusahaan ESCO dari berbagai departemen.…”
Section: Metodeunclassified